Alfonsina Storni: restrictions and strategies on her way to professionalisation (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Alfonsina Storni is a writer who has forged a position within the Argentinian literary canon, under the image of a writer who revokes sentimentalism, fatality and “feminine” poetry. Recently, the feminist-oriented literary criticism has dismantled this image finding out other areas in her literary production. This work is focused on the years in which Alfonsina Storni published her first collections of poems and started struggling for a certain position in the emerging literary field, which was mainly under male domain. Taking a gender perspective, the aim is to visualize emerging dominant, and residual cultural practices that contributed or determined her path towards becoming a professional writer, in a context of changes due to modernizing processes and the feminist movement advance.
Keywords: Alfonsina Storni; gender; professionalization; modernism; literary field